Heterozygous mutations in ZP1 and ZP3 cause formation disorder of ZP and female infertility in human. Issue 15 (22nd June 2020) - Cao, Qiqi; Zhao, Chun; Zhang, Xiaolan; Zhang, Heng; Lu, Qianneng; Wang, Congjing; Hu, Yue; Ling, Xiufeng; Zhang, Junqiang; Huo, Ran
Abstract: The human zona pellucida (ZP) is a highly organized glycoprotein matrix that encircles oocytes and plays an essential role in successful reproduction. Previous studies have reported that mutations in human ZP1, ZP2 and ZP3 influence their functions and result in a lack of ZP or in an abnormal oocytes and empty follicle syndrome, which leads to female infertility. Here, we performed whole‐exome sequencing in two probands with primary infertility whose oocytes lacked a ZP, and we identified a heterozygous mutation in ZP1 (NM_207341:c.326G>A p.Arg109His), which is situated in the N‐terminus, and a heterozygous mutation in ZP3 (NM_001110354:c.400G>A p.Ala134Thr), which is situated in the ZP domain. The effects of the mutations were investigated through structure prediction and in vitro studies in HeLa cells. The results, which were in line with the phenotype, suggested that these mutations might impede the function of cross‐linking and secretion of ZP proteins. Our study showed that the two mutations in ZP1 and ZP3 influenced the formation of the ZP, causing female infertility. Meanwhile, these data highlight the importance of the ZP1 N‐terminus in addition to the conserved domains for ZP1 function and ZP formation. Additionally, the patient with the ZP1 mutation delivered a baby following intracytoplasmic sperm injection (ICSI); thus, we suggest the targeted genetic diagnosis of ZP genes to choose appropriate fertilization methods and improve the success rate of assisted reproductive technology (ART) treatments.